Nurse educators’ perceptions of factors related to the competence of graduating nursing students - Järvinen Tiina; Virtanen Heli; Kajander-Unkuri Satu; Salminen Leena (Elsevier, 2022)
Background: Clinical practice, clinical nursing teaching, curricula, working experience and previous healthcare degrees are factors related to the competence of graduating nursing students from the points of view of nursing students and clinical mentors. However, nurse educators’ perceptions of these factors are lacking in previous studies, despite the fact that assessing student performance and competence is a core competence and one of the main duties of nurse educators.
Objectives: The aim of this study was to describe nurse educators’ perceptions of factors related to graduating nursing students’ competence.
Design: The study was conducted using a descriptive qualitative approach utilising focus group interviews in data collection.
Participants: A purposive sample consisting of 23 volunteer nurse educators from five Finnish universities of applied sciences took part in seven group interviews.
Methods: Data was collected in guided, semi-structured interviews, based on a literature review of previous studies. The data was analysed using a deductive- inductive content analysis.
Results: According to nurse educators, six main categories describing factors related to graduating nursing students’ competence were found: (1) commitment to the nursing profession, (2) experiences in healthcare, (3) learning abilities, (4) learning environments, (5) student characteristics and (6) the nurse educator’s role.
Conclusions: To ensure the adequate competence of the graduating nursing students, students’ commitment to the nursing profession and their learning abilities and should be supported, and the quality of the learning environments, especially those of study groups and successful clinical practices, should be ensured during the education.